2021
DOI: 10.1021/acs.cgd.1c00600
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of N—H···O═C Interactions in the Crystallization Mechanisms of Trisubstituted Bis-Ureas with Bulky Substituents

Abstract: Bis-ureas are generally associated with strongly bifurcated hydrogen bonds (NH···OC interactions). For this reason, a series of trisubstituted bis-ureas (TBU) with bulk substituents were designed and used as a study model to gain a better understanding of the persistence of NH···OC interactions as driving interactions of the crystallization process. The TBU molecules possess different substituents (isopropyl, benzyl, and 4-nitro-benzyl) and variations in the methylene spacer. The TBU self-assembly, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 44 publications
(85 reference statements)
0
25
0
Order By: Relevance
“…In an attempt to understand how supramolecular similarity arises and how the crystals were formed in this series of compounds, crystallization mechanisms were proposed using the supramolecular cluster demarcation and based on stabilization energy and the contact area between the molecules of the crystal. 20,39,50 Generally speaking, this takes places using a retrocrystallization process, which proposes how the crystallization occurred from the energy hierarchies of the formed crystal (obtained by SC-XRD), meaning that the most energetic dimers will likely compose the first nucleus formed during crystallization. Stage parameters are used to help understand the crystallization process by furnishing quantitative data related to each stage.…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to understand how supramolecular similarity arises and how the crystals were formed in this series of compounds, crystallization mechanisms were proposed using the supramolecular cluster demarcation and based on stabilization energy and the contact area between the molecules of the crystal. 20,39,50 Generally speaking, this takes places using a retrocrystallization process, which proposes how the crystallization occurred from the energy hierarchies of the formed crystal (obtained by SC-XRD), meaning that the most energetic dimers will likely compose the first nucleus formed during crystallization. Stage parameters are used to help understand the crystallization process by furnishing quantitative data related to each stage.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the analysis of normalized NC and NG data, we have proposed the crystallization mechanisms of a series of organic compounds to understand the crystal formation process. [30][31][32][33][34][40][41][42][43][44] The construction of a crystallization mechanism proposal involves hierarchizing supramolecular cluster dimers, mainly considering the interaction energies. The most energetic dimers are supposed to interact first, building small blocks that, through a selection process based on greater stability and greater possibility of cooperativity with other blocks, will persist and form the first aggregates that give the protocrystal.…”
Section: Supramolecular Approach and Proposed Crystallization Mechanismsmentioning
confidence: 99%
“…Our NMR studies have shown that these first blocks can already be detected while still in solution. 31,34,[42][43][44] Subsequently, larger blocks are formed, building three-dimensional networks and increasing the complexity of the systems. This approach allows observing direction growths step by step and highlighting the main interactions involved in the process.…”
Section: Supramolecular Approach and Proposed Crystallization Mechanismsmentioning
confidence: 99%
“…The differences in the types of connections provide a simple way to differentiate the target materials, helping in the search for the most strategically favourable synthetic route due to the energy involved in the processes of forming and breaking connections in the construction of superstructures [10] . More recently, an approach to better understanding the crystallization phenomenon has been reported, while considering topological and energetic factors [11] associated with these types of interactions that play a decisive role in the formation of crystals, explored as a supramolecular cluster [12–16] . The concept of supramolecular cluster creates the idea of a fixed number of molecules that provide information to help understand the supramolecular interactions of the crystalline system, that is, a cluster formed by the first coordination sphere [11] .…”
Section: Introductionmentioning
confidence: 99%
“…[10] More recently, an approach to better understanding the crystallization phenomenon has been reported, while considering topological and energetic factors [11] associated with these types of interactions that play a decisive role in the formation of crystals, explored as a supramolecular cluster. [12][13][14][15][16] The concept of supramolecular cluster creates the idea of a fixed number of molecules that provide information to help understand the supramolecular interactions of the crystalline system, that is, a cluster formed by the first coordination sphere. [11] Recently, remarkable studies have advanced and correlated theoretical and experimental data for nucleation proposals.…”
Section: Introductionmentioning
confidence: 99%